2016
DOI: 10.1371/journal.pone.0152001
|View full text |Cite
|
Sign up to set email alerts
|

What Is a Group? Young Children’s Perceptions of Different Types of Groups and Group Entitativity

Abstract: To date, developmental research on groups has focused mainly on in-group biases and intergroup relations. However, little is known about children’s general understanding of social groups and their perceptions of different forms of group. In this study, 5- to 6-year-old children were asked to evaluate prototypes of four key types of groups: an intimacy group (friends), a task group (people who are collaborating), a social category (people who look alike), and a loose association (people who coincidently meet at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 44 publications
2
42
1
1
Order By: Relevance
“…Here, we gave no background information about the groups, therefore leaving open children's perceptions. Children who perceived the groups as intimately related (e.g., families, friends) may have relied on notions of group loyalty, whereas those who conceptualized the groups as task focused (e.g., sports teams) may have relied on notions on interdependence (see Lickel et al, 2000;Pl€ otner, Over, Carpenter, & Tomasello, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we gave no background information about the groups, therefore leaving open children's perceptions. Children who perceived the groups as intimately related (e.g., families, friends) may have relied on notions of group loyalty, whereas those who conceptualized the groups as task focused (e.g., sports teams) may have relied on notions on interdependence (see Lickel et al, 2000;Pl€ otner, Over, Carpenter, & Tomasello, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Preferring “minimal” ingroup members begins early in childhood. In both classic experiments, like the Robber’s Cave [122], and more modern research [44, 123125], children prefer other people who are in their randomly assigned group.…”
Section: The Relationship Between Social Preferences and Social Categmentioning
confidence: 99%
“…In contrast, cognitive accounts focus on categorization, essentialism, and other cognitive processes that facilitate sorting individuals into social categories and learning about the properties and behaviors shared by members of the same category (8,21). Some proponents of cognitive accounts have also suggested that conceptual structures for group cognition, such as a naive theory of sociology or a folk theory of groups (11,22,23), support children's ability to identify the groups in their social environments and to learn about patterns of interactions within and across groups.…”
Section: Prior Accounts Of Igf In Minimal Groupsmentioning
confidence: 99%